Laporan latihan praktikal di Unit IT Penang Golf Resort Berhad / Mohd Nazri Ismail - Ismail, Mohd Nazri (Universiti Teknologi MARA, Kedah, 2010)
Penang Golf Resort {PGR) is a golf club situated at Bertam near Kepala Batas Pulau Pinang. PGR is built on part of SOO-acre land with total of 36 holes, managed by Penang Golf Resort Berhad, a wholly owned subsidiary of Bertam Properties Sdn Bhd. Designed by Graham Marsh, a golfing great and world-renowned golf course architect, it challenges players of all golfing capabilities and temperament with three sets of tees, tree-lined and landscaped lush fairways culminating with well-manicured verdant greens PGR cybercafe is situated inside PGR which was develop to provide internet and computer service for member as well as staff of PGR. Operated from 8.00am to 11.00pm, this cybercafe is managed under direct supervise of its operator.